Cross‐sectional study of randomly selected 18‐year‐old students showed that body mass index was only associated with sleep duration in girls. (28th February 2018) - Kjartansdottir, Ingibjorg; Arngrimsson, Sigurbjorn A.; Bjarnason, Ragnar; Olafsdottir, Anna S.
Abstract: Aim: This study investigated the associations, by sex, between sleep and adiposity, dietary habits, cardiorespiratory fitness and metabolic risk in 18‐year‐old students. Methods: We carried out a cross‐sectional study of 199 randomly chosen, healthy 18‐year‐old students (53% girls) in Iceland's capital region. The data collection took place in the winter months of 2012 to 2015. The anthropometric measurements were body mass index, waist circumference and body fat percentage. Sleep duration and dietary habits were self‐reported. Cardiorespiratory fitness was measured on a stationary bicycle. A subsample of 152 participants gave blood samples. Results: A quarter of the adolescents failed to reach the minimum recommended sleep duration of seven hours per night on weekdays. In girls, the average sleep score was associated with body mass index and waist circumference, after adjusting for cardiorespiratory fitness and unhealthy eating scores. In boys, the average sleep score was not associated with anthropometric measurements, but cardiorespiratory fitness was an independent predictor (p < 0.001). No associations were found between average sleep scores and metabolic profiles in either sex. Conclusion: Sleep duration and adiposity only appeared to be associated in girls and were independent of cardiorespiratory fitness and unhealthy eating. Sleep duration was not related to metabolic risk.